Role of DW Akademie’s Media and Information Literacy Model in Cultivating a Media-Savvy Generation - Dadakhonov Azamjon Oltmishevich (Research on Education and Media)
Media and Information Literacy (MIL) is one of the most important issues in today's mediatized world. Under the leadership of UNESCO, many international organizations in the world, as foreign donors, annually announce many projects and grants for the promotion and development of the field of MIL in the countries of the world. One of the main actors of this movement is DW Academy with various media and MIL projects in over 50 countries of the world. This research paper examines the role of DW Akademie's MIL model in shaping a media-savvy generation. The study examines the theoretical underpinnings and practical applications of the DW Akademie's MIL model and analyzes its effectiveness in fostering media literacy skills. The research takes a multifaceted approach, incorporating case studies to assess the model's impact on different demographic groups. The paper also considers the model's alignment with global education policy and proposes recommendations for its integration into broader frameworks. By examining the DW Akademie's MIL model, this research contributes to the ongoing discourse on media literacy education and provides valuable insights for educators, policymakers, and researchers. The findings offer a nuanced understanding of the model's place in cultivating a media-savvy generation capable of navigating the complexities of the information age.